Omental Infarction: A Forgotten Entity - Virendra Athavale; Rushabh Parekh; Saili Kelshikar (Journal of Clinical and Diagnostic Research, 2024)
Omental infarction is a cause of acute abdominal pain. It is a challenging diagnosis to make due to its infrequent occurrence, low awareness, and non specific presentation. It is generally recommended to manage it conservatively because of its self-limited nature. However, some physicians opt for surgical management due to the potential risk of abscess formation with conservative treatment. Omental infarction commonly occurs following torsion. The anatomical features of the omental sheet, such as its increased length, freely mobile lateral edge, and a weak blood supply, make it more susceptible to twisting along its long axis, leading to congestion. If the twist is severe enough or if there is prolonged obstruction to venous flow, arterial inflow may be compromised, resulting in infarction and potential complications like necrosis. Here, the authors present a case of a 64-year-old diabetic male who presented to the Emergency Department with acute right upper quadrant pain. He was diagnosed with omental infarction through Computed Tomography (CT) of the abdomen. The authors attempted conservative management, but his pain persisted despite analgesics. Subsequently, the authors opted for surgical intervention and performed an omentectomy. In cases of acute abdominal pain, conditions like omental infarction are often overlooked and should be considered in the differential diagnosis.